Strategi Penguatan Pendidikan Akhlak melalui Pembelajaran Tahfizh di Madrasah Ibtidaiyah - Aziz, Nur; Subando, Joko (Lembaga Yasin AlSys, 2025)
Moral education is a fundamental aspect of character formation at the primary level, particularly in Madrasah Ibtidaiyah. This article aims to analyze the role of tahfidz al-Qur’an instruction as a strategy for strengthening moral education within the madrasah environment. Using a descriptive qualitative approach through literature review, the study finds that tahfidz functions not only as a process of memorizing the sacred text but also as a medium for the internalization of moral values contained in the Qur’an. The implementation of tahfidz integrated with character development has been shown to foster religious, disciplined, honest, and responsible behavior in students. The success of this internalization process is significantly influenced by the teacher’s role as a moral exemplar, the creation of a supportive school environment, and the application of contextual learning methods relevant to students' daily lives. Therefore, tahfidz al-Qur’an serves as an effective instrument for cultivating noble character from an early age in Islamic primary education.